Impact of knowledge sharing on public sector accounting innovation performance in Vietnam - Lam Thi My Yen; Le Van Tung (Ho Chi Minh City Open University Journal of Science - Economics and Business Administration, 2022)
Knowledge sharing is a relatively new issue in the public sector, but it is very important, as evidenced by many studies in the private sector that have studied the influence of knowledge sharing on the performance of innovation. The current public accounting, which is in the process of international integration and the accrual basis of accounting reform, is one of the innovations. With the aim of helping public sector organizations improve the performance of accounting innovation, many studies have shown the important role of knowledge sharing, however, with the specificity of public sector organizations, this issue has not been implemented and verified. The mixed-method (interviewing 06 experts and a quantitative survey of 266 samples from public sector organizations in Vietnam) has been applied. The results demonstrate that knowledge sharing has no impact on the performance of accounting innovation. Instead, the creativity and receptivity of accountants have a significant impact on the performance of accounting innovation. At the same time, the biggest influencing factor that stimulates accountants’ willingness to share accounting knowledge is the support of leaders, while organizational rewards and the use of information technology did not affect the knowledge sharing of accounting staff of the units. Key findings are discussed for public organizations in Vietnam to improve accounting innovation in the context of global integration. Besides, this study discusses the policy implications of the study and describes possible future research directions.